POWER SUPPLY DEVICE AND POWER SUPPLY SYSTEM - ASADA NOBUYUKI (2022)
To provide a power supply device and power supply system that supply power to power supply targets such as a street light, a security camera, and a traffic light device, and can ensure the safety of the area even in the event of a large-scale power outage.SOLUTION: A power supply system 1 includes a power supply device 3. The power supply device 3 includes an inlet 6 capable of receiving electric power supplied from a vehicle 4. The power supply device 3 is configured to electrically connect the vehicle 4 and power supply targets 5 when the inlet 6 and the vehicle 4 are connected via a power supply cord 7. Herein, the power supply targets 5 include at least one of a traffic light 5A, a security camera 5B, and a street light 5C. As a result, in the event of a power failure, the electric power supplied from the vehicle 4 can be supplied to the power supply targets 5 comprising the traffic light 5A, the security camera 5B, the street light 5C, and the like via the inlet 6.SELECTED DRAWING: Figure 1 【課題】大規模停電時においても、街灯や防犯カメラ、信号機等の給電対象に電力を供給し、地域の安全性を確保することができる給電装置及び給電システムを得る。【解決手段】電力システム１は、給電装置３を備えている。給電装置３は、車両４から供給される電力を受電可能なインレット６を備えている。給電用コード７を介してインレット６と車両４とを接続すると、給電装置３によって、車両４と給電対象５とが電気的に接続されるように構成されている。ここで、給電対象５は、信号機５Ａ、防犯カメラ５Ｂ及び街灯５Ｃの少なくとも一つを含んでいる。これにより、停電時に、インレット６を介して、車両４から供給される電力を信号機５Ａ、防犯カメラ５Ｂ及び街灯５Ｃ等で構成された給電対象５に供給することができる。【選択図】図１